Integrated Technical, Economic, and Environmental Optimization of Solar-Based Green Hydrogen Production - Nainggolan, Denny Hendrik (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The increasing urgency of climate change mitigation and the global transition toward sustainable energy systems have accelerated interest in green hydrogen as a clean energy carrier. Green hydrogen produced through water electrolysis powered by solar energy offers a promising pathway to decarbonize industrial, transportation, and energy storage sectors. However, challenges related to energy conversion efficiency, production cost, and environmental sustainability remain major barriers to large-scale deployment. This study aims to analyze and optimize green hydrogen production from solar-powered water electrolysis by integrating technical, economic, and environmental perspectives. The research employs a qualitative literature review method, synthesizing peer-reviewed studies published between 2015 and 2025. Data were collected through a systematic review process following the PRISMA framework and analyzed using thematic content analysis. The findings indicate that technical optimization through high-efficiency photovoltaic systems, advanced electrocatalysts, and system integration can significantly improve solar-to-hydrogen efficiency. Economic analyses reveal that reductions in photovoltaic and electrolyzer costs, optimal system sizing, and strategic site selection are key to lowering the levelized cost of hydrogen. Environmentally, life cycle assessments demonstrate substantial greenhouse gas emission reductions compared to fossil-based hydrogen pathways. An integrative optimization approach is essential to ensure balanced performance, cost-effectiveness, and sustainability.